Analisis Kepuasan Masyarakat Peserta Program Sarase Warga Sukowati (Saraswati) terhadap Pelayanan di RSUD dr. Soehadi Prijonegoro Kabupaten Sragen (Studi Pelayanan Pasien Rawat Inap) - Jayanti, Anisa Novia; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Society satisfaction is a condition where the service performance received is accordance with or greater than the people expectation of the public service. In order that the implementation of health service provider for poor people can run well and be optimum in improving the level of public health, the Government of Sragen held a regional health insurance program namely Sarase Warga Sukowati (Saraswati). The public health service providers in this study is RSUD dr. Soehadi Prijonegoro in Sragen Regency. The research methodology used was SERVQUAL to measure the satisfaction of Saraswati Program Member based on their expectation on the performance of service which is run by Parasuraman et al (1985). The type of research is descriptive analysis through quantitative approach by involved 90 respondents, namely the Saraswati Program Member which was hospitalized. Then the data analysis technique used Importance Performance Analysis (IPA) in form of gap analysis with compatibility level and cartesian diagram. The result of the study indicates that based on the service quality theory by Parasuraman et al in the dimension of service quality: tangibles, reliability, responsiveness, assurance and emphaty, the overall average dimension of compatibility level is amounted to 90,01% so that it is categorized as satisfying. While the analysis result of cartesian diagram indicates that the indicator of the ease of procedure, waiting room availability and the hospitality of medical personnels are categorized to A quadran so that the performance is less satisfying. Suggestions that the writer can give are to add customer service counters that explain the procedures and assist in completing the inpatient service facilities and provide optimum waiting room for television media facilities, as well as excellent training services on how to tidy, friendly and competent in patient positions; Service ethics and establishment of attitudes/ attitudes of service; Patient type tip; And service role play.